2017
DOI: 10.1002/j.0022-0337.2017.81.2.tb06259.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Oral‐Systemic Health on Advancing Interprofessional Education Outcomes

Abstract: The aim of this study was to evaluate the effectiveness of an interprofessional education (IPE) clinical simulation and case study experience, using oral-systemic health as the clinical population health example, for nurse practitioner/midwifery, dental, and medical students' self-reported attainment of interprofessional competencies. A pretest-posttest evaluation method was employed, using data from the Interprofessional Collaborative Competency Attainment Scale (ICCAS) completed by two large cohorts of nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 18 publications
6
51
0
Order By: Relevance
“…A recent study aimed to assess the usefulness of an IPE clinical simulation and case study experience for nurse practitioner (NP)/midwifery (MW), medical, and dental students using oral systemic health and they included self-reported completion of interprofessional competencies ( 31 ). A total of 318 students participated in the IPE experience in 2013 and 300 students in 2014.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study aimed to assess the usefulness of an IPE clinical simulation and case study experience for nurse practitioner (NP)/midwifery (MW), medical, and dental students using oral systemic health and they included self-reported completion of interprofessional competencies ( 31 ). A total of 318 students participated in the IPE experience in 2013 and 300 students in 2014.…”
Section: Discussionmentioning
confidence: 99%
“…A moderate correlation was found between students' improvement in knowledge and their actual clinical skills. Other studies on interprofessional children's oral health education also involved a combination of didactics and clinical simulations; however, limited studies measured participants' clinical skills objectively on a set criterion [11,17,18,28]. No significant correlation was found between students' improvement in confidence and attitude and their clinical skills.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies have shown successful incorporation of oral health training as part of interprofessional education; however, there is a lack of studies on the evaluation of clinical knowledge and the skills of these students [12,13,18]. The aims of this study are (1) to develop an interprofessional curriculum to improve knowledge, attitude, and confidence in providing children's oral health care, (2) to assess students' clinical competency in assessing children's oral health, and (3) to evaluate whether improved knowledge is associated with actual clinical skills.…”
Section: Introductionmentioning
confidence: 99%
“…18 This is also promising as studies report that clinical practice patterns are sustained postgraduation. 19 The role of dental and medical education in patient awareness, provider knowledge, and evolution of practice cannot be underestimated. 20 It has been documented that combining didactic and interactive teaching methods is more effective on the learner than either alone, according to a Cochrane review of continuing medical education.…”
Section: Discussionmentioning
confidence: 99%